Tax Enforcement and Protection of Taxpayers Rights in Uganda - Oscar Kambona (CV. Proaksara Global Transeduka, 2025)
The overall aim of this article is to analyse the protection of Taxpayers rights in Uganda during resolution of tax disputes. Taxation is increasingly becoming the primary source of government revenue around the world and is the means used to support and fund government goods and services.To increase revenue mobilization through enhanced tax collection, the tax administration body, the Uganda Revenue Authority (URA) has certain enforcement powers. In the course of enforcements, disputes, between tax authority and the taxpayer are bound to occur and in fact do occur. In Uganda, the Courts have been expressly empowered by statutory legislation to demand that an aggrieved taxpayer deposit 30% of the contested amount pending finalization of the dispute.While the intention of the requirement seems to cater for raising of revenue to ensure continuity in government operations, this however is inherently predisposed to infringe taxpayer’s right to property as well as seek administrative justice, and that this affects taxpayer compliance. Ultimately, the article emphasizes the need for a full realization of the taxpayer’s rights and of the inseparable nexus between human rights and tax compliance.